EXPLORATIVE-EXPERIENCE-BASED TRANSLATION PROJECT FOR TRANSLATING-INTERPRETING CLASS - Andy Bayu Nugroho (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2013)
Some explorative methods have been done in teaching translation. The approach used in this method is based on the writer’s experience during his teaching. This method is aimed at (1) introducing students to translating business, (2) giving more exposure to students in practicing translating texts, (3) exploring students’ experiences in applying translation theories and strategies, and (4) developing process-based translation research to extend translation teaching methods. The explorative-experience-based translation project is a teaching method in translating-interpreting class which allows students to explore their experience in the ‘real’ translation activities and industry as well as to apply their knowledge on translation theory and strategies of translation. The steps performed in this method are (1) giving brief description to students about business in translation, (2) introducing them to publishers, (3) guiding them in writing proposals for translation field work, (4) conducting advisory during the students’ field work (consisting class discussion and problem solving), (5) interviewing students’ difficulties during their projects, (6) recording students’ major problems (in terms of sentence and text types), and (7) expanding this procedure with a process-based research by the teacher or lecturer. The students involved in this class should have taken some basic courses as introduction to translation (translation studies), translating practice, or other related courses available in the department. Some opportunities and treats are explored through this method. These can enhance teachers’ strategy and method in translating-interpreting class. Keywords: experience, process-based research, translation business, translating project, translation strategy